Hotel internet marketing channels and purchase decision / Amirul Muidz Amrahi and Salleh Mohd Radzi - Amrahi, Amirul Muidz; Mohd Radzi, Salleh (2014)
This paper aims to investigate the relationship between hotel internet marketing channels and customer purchase decision of 5star hotels in Kuala Lumpur. A quantitative approach used in this paper where instrumentation design was based on previous research methodology. Questionnaires were distributed to all 5 star hotels in Kuala Lumpur official Facebook fan page using an online survey provider. From the findings, it was found that there is a significant relationship between hotel internet marketing channels and purchase decision. This paper only focused on 5 star hotels in Kuala Lumpur, and it is suggested that the study could be conducted covering all 5star hotels in Malaysia for a better scenario of the industry.